Los partidos y la representación política en proceso de cambio. (2012)
This article points to two limitations in the Latin American literature that analyzes the so-called crisis of political representation. The first one comes from the ambiguity that the term political party as a concept is dealt; and the second one stands out the scarce familiarity of the authors with the new perspectives on the political representation published in English. The diagnostic on the mentioned crisis; it is claimed; would gain; on one hand; if it is made from a quantifiably concept of political party; and on the other hand; if it incorporates some elements of the new; just mentioned; perspectives